2011
DOI: 10.1089/dia.2011.0085
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy Started at the Time of Diagnosis: Effects on Glycemic Control and Pancreatic β-Cell Function in Type 1 Diabetes

Abstract: Initiation of insulin pump therapy at diagnosis improved glycemic control, was well tolerated, and contributed to improved patient satisfaction with treatment. This study also suggests that earlier use of pump therapy might help to preserve residual β-cell function, although a larger clinical trial would be required to confirm this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
2
23
0
1
Order By: Relevance
“…22,23 Some subsequent intervention studies, but with a short follow-up duration (£24 months), showed that an early pump commencement has a favorable effect on residual b-cell function and glycemic control 24,25 and that using a sensoraugmented pump led to similar results. 26,27 It is possible that the better glycemic control observed in our study in the first and second quartiles is related to a better preservation of residual b-cell function; in other words, an early pump commencement could prolong the honeymoon phase.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Some subsequent intervention studies, but with a short follow-up duration (£24 months), showed that an early pump commencement has a favorable effect on residual b-cell function and glycemic control 24,25 and that using a sensoraugmented pump led to similar results. 26,27 It is possible that the better glycemic control observed in our study in the first and second quartiles is related to a better preservation of residual b-cell function; in other words, an early pump commencement could prolong the honeymoon phase.…”
Section: Discussionmentioning
confidence: 99%
“…8,15 However, among the seven participating pediatric diabetes centers, the incidence of pump use early in the course of childhood diabetes varied. Racial/ethnic group, insurance status, and household income appeared to influence whether …”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, initiation of insulin pump therapy at diagnosis has been shown to improve glycemic control. 8 Over the past 10 years, increasing numbers of children and adolescents with T1D have been placed on insulin pump therapy, and large numbers of clinical outcome studies have confirmed the benefits of pump therapy in the pediatric age group. [3][4][5]9,10 Nevertheless, data are limited regarding realworld patterns of pump use during the first year of treatment of T1D in children and adolescents and the clinical and socioeconomic factors that are associated with early use of pump therapy.…”
Section: Which In Turnmentioning
confidence: 99%
“…It has also been suggested that the type of insulin treatment may modulate the duration of this phase. A strict glycaemic control either with basal bolus [24] or with an insulin pump [25] has been shown to extend the honeymoon phase.…”
Section: The Remission Phase In Paediatric T1dmentioning
confidence: 99%